Control of base pressure with micro jets for area ratio 2.4 - Ashfaq, Syed; Khan, Sher Afghan; Rathakrishnan, Ethirajan (Praise Worthy Prize, 2014)
This paper presents the results of experimental studies to control the base pressure from a convergent nozzle to ascertain the effect of level of expansion in a suddenly expanded flow at sonic Mach number. An active control in the form of four micro jets of 1 mm orifice diameter located at 900 intervals along a pitch circle diameter of 1.3 times the nozzle exit diameter in the base region was employed to control the base pressure. The area ratio (ratio of area of suddenly expanded duct to nozzle exit area) studied is 2.4. Experiments were conducted for nozzle pressure ratio (NPR) from 1.5 to 3, in steps of 0.5 (i.e. for NPR 1.5, 2.0, 2.5 and 3.0). The L/D ratio of the duct was varied from 10 to 1, and tests were conducted for L/D 10, 8, 6, 5, 4, 3, 2 and 1. It is evident from the results that the flow field downstream of the reattachment-redevelopment is very complex. From the investigation it is found that unlike passive controls the favourable pressure gradient does not ensure augmentation of the control effectiveness for active control in the form of micro jets. To study the influence of micro jets on the quality of flow in the enlarged duct wall pressure was measured and it is found that the micro jets do not disturb the flow field in the duct.